145k views
4 votes
1. Make sure you show all of your work!

Change the quadratic to factored form.
g(x)=2x² – 3x-5


User Myster
by
6.1k points

2 Answers

2 votes

Answer:

g(x) = (2x - 5)(x + 1)

Explanation:

g(x) = 2x² - 3x - 5

1. find two numbers that add up to -3 and has the product of -10: -5 & 2.

2. Put them in the stead of -3x: 2x² - 5x + 2x - 5

3. Factor: (2x - 5)(x + 1)

User Submonoid
by
5.6k points
7 votes

Answer:

g(x) = (2x - 5)(x + 1)

Explanation:

g(x) = 2x² – 3x-5

2 * (-5) = -10

and

(-5) + 2 = - 3

so

2x² – 3x-5

= 2x² + 2x - 5x - 5

= 2x(x + 1) - 5(x + 1)

= (2x - 5)(x + 1)

Answer

g(x) = (2x - 5)(x + 1)

User Mogoman
by
6.6k points